ANALISIS KESULITAN SISWA DALAM MEMBACA SURAT PENDEK DI SDN 1 BLANGKEJEREN - Syifa Salsabila; Hadini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Quranic learning in elementary schools plays a crucial role in shaping students' character, morals, and religious identity from an early age. In addition to instilling Islamic values, this learning also improves Arabic reading and comprehension skills. However, in practice, students still experience difficulties in reading the Quran correctly, particularly in reading short surahs at SDN 1 Blangkejeren, particularly in the aspects of makharijul huruf and tajwid. This study aims to analyze the types of student difficulties, the causal factors, and the teachers' efforts to overcome them. The study used a qualitative approach with eight fifth-grade students selected purposively, and data collection through interviews, observations, and tests. The results showed five main forms of difficulties: distinguishing hijaiyah letters, understanding connected letters, distinguishing between long and short readings, pronouncing makharijul huruf, and applying tajwid rules. These difficulties are influenced by students' lack of focus, incorrect reading habits, minimal exposure to Quranic recitation outside of school, and limited Islamic Religious Education (PAI) teachers. Teachers' efforts include the use of hijaiyah letter cards, drill methods, and providing reading examples and direct correction.